A World of Regions : Asia and Europe in the American Imperium - Katzenstein, Peter J. (Book collections on Project MUSE., 2005)
In contrast to those who believe in the inevitable march of globalisation, Peter Katzenstein argues that, since the end of the Cold War, regions, not nation-states, have become critical to contemporary world politics.